Tradisi Hafalan Al-Qur’an Di Yogyakarta Perspektif Sosiologi Pengetahuan (Kajian Living Qur’an) - Fuji Nur Iman, Taufikkurrahman (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2020)
The process of safeguarding the Koran at the time of the Prophet Muhammad with memorization was formed from a strong oral tradition among the Arab community at that time, apart from that some studies also found that the written tradition at that time was not too developed, because few friends were involved in the process of writing al -The Qur'an from the time of the Prophet Muhammad to the time of the four Khulafaur Rashidun can be used as an indication that not many friends are able to write well. Recent research after the discovery of the manuscript of the Koran in the Great Mosque of San'a which turned out to be a lot of palimsests also contributed to the argument that the late writing tradition developed at that time. Based on this horizon, preassure for memorization becomes natural for Muslims at this time. In this article, we will discuss al-Qur'an memorization at Pon-Pes al-munawair Huffadz I, which was applied in the past and is transmitted for the present era.